P003 Identification of an intestine-derived ex-Trm population in the blood of healthy individuals and patients with Inflammatory Bowel Disease. (21st January 2022) - Rodger, B; Gordon, H; Hoti, I; Stagg, A; Lindsay, J
Abstract: Background: Tissue-resident memory T cells (Trm) persist in peripheral tissues and contribute to pathogen clearance and inflammation. Trm can re-enter the circulation (ex-Trm) and give rise to new effector and Trm populations. Skin-derived ex-Trm can be identified in human blood based on co-expression of the residency marker CD103 and cutaneous leukocyte antigen (CLA), a skin-tropism marker. The existence of ex-Trm derived from the gut would have implications for inflammatory bowel disease (IBD) and its treatment targeting the recruitment of circulating gut-homing cells. Methods: Peripheral blood and colonic biopsies were taken from healthy volunteers and patients with IBD (Crohn's disease or ulcerative colitis). PBMCs and cells isolated from biopsies by enzymatic digestion were analysed by multi-colour flow cytometry. Results: More than 80% of colonic αβT cells were Trm, as defined by CD69 expression, in health and IBD; there was no significant increase in cells with a non-resident phenotype in inflamed tissue. Few CD4+ Trm co-expressed CD103. In contrast, CD8+ Trm comprised CD103+ and CD103- subsets, and CD69+CD103- cells were significantly reduced in IBD. Increased staining for KLRG1 and the cytotoxicity-associated protein perforin, indicated a more effector-like Trm phenotype in IBD. Putative gut-derived ex-Trm were identified amongst TCRαβ+CD45RA- blood cells as a β7++CD103+ population, indicative of cells expressing both α4β7 and CD103(α E )β7 integrin complexes. A separate CD103β7+α4β7 population defined by 1:1 expression of CD103 and β7 contained CLA+ skin ex-Trm. Gut ex-Trm comprised 0.3% of circulating CD8 + T cells (range 0.02–1.4%), and 1.2% of CD4 + T cells (range 0.3–3%). Gut and skin ex-Trm were phenotypically similar; both expressed the residency associated markers CD9 and CD101 but lacked CD69 expression. Gut ex-Trm were phenotypically distinct from both the traditional gut-trophic population (α4β7+CD103-CD45RA) and from naïve T cells. The proportion of gut ex-Trm did not differ between health and IBD. However, gut-derived ex-Trm were significantly reduced, relative to skin-derived ex-Trm, in Crohn's disease, but not ulcerative colitis, when compared with health. Conclusion: A putative gut-derived ex-Trm population can be identified in both healthy and IBD peripheral blood, with IBD-associated changes identified in this population and intestinal Trm. Circulating ex-Trm could link discreet areas of intestinal inflammation in Crohn's disease and there is a selective loss of the gut ex-Trm population from the blood of these patients. The role of ex-Trm in IBD merits further study.